Candidates, Congress, and the American Democracy. (University of Michigan Press, 2010)
In Candidates, Congress, and the American Democracy Linda L. Fowler provides a wide-ranging examination of candidacy as a source of both stability and change in U.S. politics. An expert on political candidates, she brings a novel perspective to the topic by emphasizing that candidates are necessary instruments for popular control of government. Fowler maintains that the ambitions of individual candidates are essential to the functioning of the nation's constitutional system and are important factors in its political history. She traces the influence of candidates in fostering electoral competition, promoting the representation of such newly mobilized groups of citizens as women and ethnic minorities, and transforming political institutions and parties. Despite the importance of candidacy, the institution is poorly understood because both scholars and voters tend to limit their focus on candidates to the narrow context of election campaigns. The author argues that a broader view reveals how candidates are linked to a variety of trends and contradictions in contemporary U.S. politics.